Penerapan Strategi Pembelajaran Aktif untuk Meningkatkan Motivasi Belajar Siswa SD/MI - Meli Ramadani; Dina Musarofah; Nu'mal Aqilah; Oman Fahrurohman (PT. Hasba Edukasi Mandiri, 2025)
This study discusses the implementation of various active learning strategies to enhance students’ learning motivation in elementary and Islamic elementary schools (SD/MI). The research employs a qualitative approach using literature study methods, analyzing theories, concepts, and previous research related to active learning. The discussion highlights four main strategies: Active Learning through group discussions, Learning by Doing or learning through direct practice, Game-Based Learning, and Project-Based Learning. The results of the literature review show that these strategies successfully create interactive, enjoyable, and meaningful learning experiences for students. By engaging directly in the learning process, students demonstrate higher intrinsic motivation, self-confidence, and critical as well as collaborative thinking skills. This research emphasizes the essential role of teachers as creative facilitators in designing student-centered learning activities, making the educational process in elementary schools more effective, engaging, and inspiring.